English Medium Instruction in the Russian University - T. B. Alenkina (Moscow Polytechnic University, 2020)
The 21 century is the time of globalization, which is manifested in the extensive use of the English language as the language of science and education. In the time of the high level of academic mobility and the great number of the English-language programs, the course "English Medium Instruction" has acquired its international reputation. According to the research conducted by the British Council, 55 countries worldwide became EMI countries. Russia was not a member. However, Russia also experiences the world trend of internationalization of education, thus the linguoprofes-sional competence plays a significant role in the learning process. Realization of the interdisciplinary approach to education has been the Russian case study of the course "English Medium Instruction" in the leading research university MIPT. The article considers the case of cooperation of the teacher with the course participants - MIPT faculty - in the process of the writing up of the syllabus. In the course of study, participants got interested in the issues of academic writing - English for research publication purposes (Research Writing) and Student Writing as the constituent and mandatory part of academic courses. Course participants considered the macrostructure of the professionally-oriented genres of writing - a research article and its types - and the most frequent difficulties and errors that occur in writing. Course participants got the answers how to integrate the writing tasks in their own course in the workshop called "Student Writing" addressing the typical student genres of data report, summary, annotated bibliography, thesis project. Course participants discussed how to create a writing task assignment in an interesting and professional way, what research skills are required for students, what are the evaluation criteria, and if it is necessary to assess the language errors and how. One more way of addressing the academic discourse was the genre of presentations. Being a hybrid genre that includes an oral part and a written part, presentations have a great learning potential, which makes it possible to compare and contrast special features of an informal and formal style. By the end of the course several participants could make some changes and even rewrite their syllabus. The author hopes that such a course with CLIL component will find its place in the Russian universities.